Effect of milling time on microstructure and mechanical properties of Cu–Ni–graphite composites. (11th September 2017) - Wang, Yiran; Gao, Yimin; Li, Yefei; Zhang, Chao; Huang, Xiaoyu; Zhai, Wenyan
Abstract: Cu–Ni–graphite composites are intended for application in switch slide baseplate materials. The microstructure of the composites depends strongly on the ball milling time, and a suitable time can significantly improve the properties of the Cu–Ni–graphite composites. In this study, a two-step milling method was employed. The morphology evolution and microstructural features of the powder was characterized at different milling times. Afterwards, the Cu–Ni–graphite composites were prepared in the process of cold pressing, sintering, re-pressing and re-sintering as a function of the different milling times. Finally, both the microstructure and mechanical properties of the Cu–Ni–graphite composites are discussed. The results show that no new phase was generated during the milling process. The morphology evolution of the mixture of Cu/Ni powder changed from spherical-like to cubic-like, plate-like and flake-like with an increasing milling time. The microstructure of the composites consisted of α -phase and graphite. The boundary area and quantity of pores changed as the milling time increased. The relative density, hardness and flexural strength reached maximum values at 15 h of milling time.